PROBLEMATIC ISSUES OF CREATING A LIMITED LIABILITY COMPANY - Бежевец, Алла; Невечеря, София (SWorldJournal, 2021)
The article faces problematic issues related to the creation of such a legal entity as a limited liability company. The analysis is made on the basis of the legislation of Ukraine. Moreover, not only the current regulations were taken into account, but al